Ecopoetics : the language of nature, the nature of language - Knickerbocker, Scott (University of Massachusetts Press, 2012)
"Ecocritics and other literary scholars interested in the environment have tended to examine writings that pertain directly to nature and to focus on subject matter more than expression. In this book, Scott Knickerbocker argues that it is time for the next step in ecocriticism: scholars need to explore the figurative and aural capacity of language to evoke the natural world in powerful ways. Ecopoetics probes the complex relationship between artifice and the natural world in the work of modern American poets--in particular Wallace Stevens, Elizabeth Bishop, Richard Wilbur, and Sylvia Plath. These poets relate to nature as a deep wellspring of meaning, although they all avoid using language the way most nature writers do, merely to reflect or refer directly to the world. Each of these poets, in his or her own distinct way, employs instead what Knickerbocker terms sensuous poesis, the process of rematerializing language through sound effects and other formal devices as a sophisticated response to nonhuman nature. Rather than attempt to erase the artifice of their own poems, to make them seem more natural and thus supposedly closer to nature, the poets in this book unapologetically embrace artifice--not for its own sake but in order to perform and enact the natural world. Indeed, for them, artifice is natural. In examining their work, Knickerbocker charts a new direction for ecocriticism."--Project Muse